Workplace and home smoking restrictions and racial/ethnic variation in the prevalence and intensity of current cigarette smoking among women by poverty status, TUS-CPS 1998–1999 and 2001–2002. (11th August 2006) - Shavers, Vickie L; Fagan, Pebbles; Jouridine Alexander, Linda A; Clayton, Richard; Doucet, Jennifer; Baezconde-Garbanati, Lourdes
Abstract : Study objective: Recognition of the health consequences of exposure to environmental tobacco smoke has led government agencies and many employers to establish policies that restrict cigarette smoking in public and workplaces. This cross sectional study examines the association of workplace smoking policies and home smoking restrictions with current smoking among women. Design: Participants were employed US women ages 18–64 who were self respondents to the 1998–1999 or 2000–2001 tobacco use supplement to the current population survey supplements. Cross tabulations and multivariate logistic regression analyses examine the association of selected demographic characteristics, occupation, income, workplace and home smoking policies/restrictions with current smoking, consumption patterns, and quit attempts among women by poverty level for five race/ethnic groups. Main results: The prevalence of either having an official workplace or home smoking policy that completely banned smoking increased with increased distance from the poverty level threshold. A complete ban on home smoking was more frequently reported by African American and Hispanic women although Hispanic women less frequently reported an official workplace smoking policy. In general, policies that permitted smoking in the work area or at home were associated with a higher prevalence of current smoking but this varied by poverty level and race/ethnicity. Home smoking policies that permitted smoking were associated with lower adjusted odds of having a least one quit attempt for nearly all poverty level categories but there was no association between having one quit attempt and workplace policies. Conclusion: Home smoking policies were more consistently associated with a lower prevalence of current smoking irrespective of poverty status or race/ethnicity than workplace policies. These findings underscore the importance of examining tobacco control policies in multiple domains (work and home) as well as by race/ethnicity and socioeconomic position.